Floating-embedded stems reduce tibial stress shielding in total knee revision arthroplasty - Dominic Schaefer; Artur Barsumyan; Kambiz Roshanghias; Jan Adriaan Graw; Christian Soost; Wolfgang Richter; Jonas Knoche; Arne Ohrndorf; Rene Burchard (Journal of Orthopaedic Surgery and Research)
Abstract Background Total knee arthroplasty (TKA) is one of the most common orthopaedic procedures and the number of patients which undergo TKA will continue to rise in the coming years. Consecutively, the number of necessary revision surgeries will increase. One of the main reasons for revision surgery is aseptic loosening because of a so-called stress-shielding effect. Typically, revision of a primary TKA is done from a bicondylar surface replacement to a stem-anchored prosthesis, which, due to higher stress-shielding, have a shorter survival time than non-stem-anchored systems. Similar to endoprosthetic treatment in pediatric tumor orthopedics, non-ingrown cementless stems can be used. The study aim was to investigate whether this concept can also be applied to reduce stress-shielding in the tibial metaphysis after revision TKA in adults. Methods Six tibial biomechanical bone with stemmed tibial TKA components were implanted using surface cementing and a floating-embedded stem or classic full cementing. After implantation, axial force was applied in such a way that the same load was generated as during walking. Two high-resolution cameras and illumination spots were used to record changes on the bone surface circumferentially in three regions of interest and from three different views. Results With regard to the fixation method, a significant difference could be demonstrated in the metaphyseal and in the middle region around the stem (p < 0.001). At the tip of the stems, the reduction of strain energy density showed a stress shielding reduction for the floating-stemmed models in two of three views (ventromedial p = 0.002, lateral p = 0.398, and dorsal: p = 0.027). Conclusions In revision surgery after TKA, the use of floating-embedded, uncemented stems without bony ingrowth shows significant reduction of metaphyseal stress-shielding within the proximal tibia. This technique could be a viable alternative to prevent early aseptic loosening and should be examined in future in-vivo studies.